2022
DOI: 10.1016/j.isci.2021.103683
|View full text |Cite
|
Sign up to set email alerts
|

Effects of top-down influence suppression on behavioral and V1 neuronal contrast sensitivity functions in cats

Abstract: Summary To explore the relative contributions of higher-order and primary visual cortex (V1) to visual perception, we compared cats' behavioral and V1 neuronal contrast sensitivity functions (CSF) and threshold versus external noise contrast (TvC) functions before and after top-down influence of area 7 (A7) was modulated with transcranial direct current stimulation (tDCS). We found that suppressing top-down influence of A7 with cathode-tDCS, but not sham-tDCS, reduced behavioral and neuronal contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 173 publications
(329 reference statements)
2
16
0
Order By: Relevance
“…Numerous studies have shown that transcranial direct current stimulation (tDCS) is a reliable non-invasive tool that can reversibly modulate neuronal excitability in the stimulated local brain region, with anode (a)-and cathode (c)-tDCS, respectively, enhancing and suppressing neuronal activity for a long-lasting (60-90 min) effect (Nitsche and Paulus, 2001;Schweid et al, 2008;Stagg et al, 2009;Monte-Silva et al, 2010;Bachtiar et al, 2015). Our recent investigations also demonstrate that c-and a-tDCS with the current intensity of 1 mA and a period of 15 min, respectively, decreases and enhances neuronal excitability with the effect confined in the stimulated cortical area and lasted for 60-70 min (Zhao et al, 2020;Ding et al, 2021Ding et al, , 2022. The current study will use tDCS tool to modulate top-down influence and observe concurrent change of both behavioral performance in orientation identification and the response selectivity of V1 neurons for stimulus orientations.…”
Section: Introductionmentioning
confidence: 81%
“…Numerous studies have shown that transcranial direct current stimulation (tDCS) is a reliable non-invasive tool that can reversibly modulate neuronal excitability in the stimulated local brain region, with anode (a)-and cathode (c)-tDCS, respectively, enhancing and suppressing neuronal activity for a long-lasting (60-90 min) effect (Nitsche and Paulus, 2001;Schweid et al, 2008;Stagg et al, 2009;Monte-Silva et al, 2010;Bachtiar et al, 2015). Our recent investigations also demonstrate that c-and a-tDCS with the current intensity of 1 mA and a period of 15 min, respectively, decreases and enhances neuronal excitability with the effect confined in the stimulated cortical area and lasted for 60-70 min (Zhao et al, 2020;Ding et al, 2021Ding et al, , 2022. The current study will use tDCS tool to modulate top-down influence and observe concurrent change of both behavioral performance in orientation identification and the response selectivity of V1 neurons for stimulus orientations.…”
Section: Introductionmentioning
confidence: 81%
“…Furthermore, our recent studies show that suppression of top-down influence decreases the neuronal contrast sensitivity in the V1 cortex. This top-down suppression may be mediated by a stronger effect of internal noise elevation than of external noise admission at the perceptual template level [ 48 ], whereas it may occur through a larger effect in the reduction of response gain than of contrast gain on the contrast-response function of V1 neurons [ 32 ], and this top-down influence in response gain may relate to alterations in excitatory glutamatergic neurotransmission [ 103 105 ]. Finally, recent studies suggest that increased GABAergic inhibition may underlie noise filtering in the visual signal perception [ 106 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Equivalent internal noise can be estimated by comparison to the effects of external noise ( N ext ) added in the stimulus. By measuring the observer's performance in the detection of visual signals with different amounts of external noise, the PTM analysis can identify three pure mechanisms of (1) stimulus enhancement (equivalent to internal additive noise reduction), (2) external noise exclusion and (3) internal multiplicative noise suppression ( Figure 4 ), or a mixture of these mechanisms in attention [ 38 , 42 ], perceptual learning [ 44 46 , 58 ], top-down influence [ 48 ], and brain development [ 63 ]. To assess the relative contributions from each or combinations of the noise sources to SS effect on neuronal contrast sensitivity, three weighting coefficients A a , A f , and A m corresponding to the noise source N a , N ext , and N m , respectively, were added in the original PTM equation to fit neuronal TvC functions obtained with and without surround stimuli: where C τ represents threshold contrast at the d ′ performance level; N a , N ext , N m , β , and γ denote, respectively, the standard deviation of internal additive noise, the standard deviation of external noise, the proportional constant of multiplicative noise, the gain of the perceptual template, and the exponent of the nonlinear transducer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations